Association of transfusion red blood cell storage age and blood oxygenation, long-term neurologic outcome, and mortality in traumatic brain injury. Issue 5 (November 2015) - Yamal, José-Miguel; Benoit, Julia S.; Doshi, Pratik; Rubin, Maria Laura; Tilley, Barbara C.; Hannay, H. Julia; Robertson, Claudia S.
Abstract : BACKGROUND: The effect of red blood cell (RBC) storage on oxygenation in critically ill patients is still unknown. The objective of this study was to determine the association of RBC storage with oxygenation, long-term neurologic recovery, and death after traumatic brain injury. METHODS: We used data from a 2 × 2 factorial randomized controlled trial of administration of erythropoietin or placebo and of assignment to transfusion threshold of less than 7g/dL or less than 10 g/dL in neurosurgical intensive care units in two US Level 1 trauma centers. Patients had severe traumatic brain injury with closed head injury, were unable to follow commands, and were enrolled within 6 hours of injury. Blood oxygenation 1 hour after the transfusion as measured by jugular venous oxygen saturation (n = 59) was the primary outcome. Secondary outcomes were brain tissue oxygenation (n = 77), 6-month Glasgow Outcome Scale (GOS) score (n = 122) collected using a structured interview and dichotomized into favorable (good recovery or moderate disability) or unfavorable outcome (severe disability, vegetative state, or dead), and mortality (n = 125). RBC age was defined as the maximum age of RBCs over all units in one transfusion per patient. For long-term outcomes, RBC age was defined as the mean age over all units given. RESULTS: We failed to detect an association of RBC age with jugular venous oxygen saturation (linear regression β = 1.59; 95% confidence interval [CI], −2.99 to 6.18; p = 0.49), brain tissue oxygenation (linear regression β = 0.20; 95% CI, −0.23 to 0.63; p = 0.36), GOS score (odds ratio, 1.37; 95% CI, 0.53–3.57; p = 0.52), and mortality (hazard ratio, 1.35; 95% CI, 0.61–2.98; p = 0.46). CONCLUSION: Limitations of this study include the fact that the RBC ages were not randomized, although this was a prospective study. We conclude that older blood does not seem to have adverse effects in severe traumatic brain injury. LEVEL OF EVIDENCE: Prognostic study, level III. Abstract : Supplemental digital content is available in the text.